Model Hidrolika untuk Analisis Efektifitas Penyekatan Kanal di Lahan Gambut - Sigit Sutikno; Eka Saputra; Muhamad Yusa (JURNAL TEKNIK UNILAK, 2021)
Peatland fires are a recurring phenomenon and become the biggest problem in peatland protection in Indonesia. Generally, peatlands in the dry season have limited water availability that may cause drought and fire. On the other hand, in the rainy season, the water in the canals is excessive that may cause floods. To overcome this problem, canal blocking should be made. This research simulates the water profile along the canal by hydraulic modeling using HEC-RAS to understand the effectiveness of canal blocking. Canal blocking at Sungai Tohor village was picked up as research site for modelling. The calibration process, this study used discharge measurements data that was measured repeatedly at dry season and rainy season. The modeling was simulated on several scenarios in the dry and rainy season with the goal of ground water depth was not lower thans 40 cm. The results of this study indicate the application of the hydraulic model at the calibration stage obtained values of R = 0.9981 and RMSE = 0.02503, Manning's coefficient of roughness was taken as 0.04. The model can predict well the water profile along the canal if the conditions without canal blocking or canal blocking conditions are in the dry season and the rainy season.